Controlled Synthesis of Heterotrimetallic Single‐Chain Magnets from Anisotropic High‐Spin 3 d–4 f Nodes and Paramagnetic Spacers. Issue 1 (7th December 2012) - Yao, Min‐Xia; Zheng, Qi; Qian, Kang; Song, You; Gao, Song; Zuo, Jing‐Lin
Abstract By using the node‐and‐spacer approach in suitable solvents, four new heterotrimetallic 1D chain‐like compounds (that is, containing 3d–3d′–4f metal ions), {[Ni(L)Ln(NO3)2(H2O)Fe(Tp*)(CN)3]⋅2 CH3CN⋅CH3OH}n (H2L=N, N′‐bis(3‐methoxysalicylidene)‐1, 3‐diaminopropane, Tp*=hydridotris(3, 5‐dimethylpyrazol‐1‐yl)borate; Ln=Gd (1), Dy (2), Tb (3), Nd (4)), have been synthesized and structurally characterized. All of these compounds are made up of a neutral cyanide‐ and phenolate‐bridged heterotrimetallic chain, with a {FeCNNi(OLn)NC}n repeat unit. Within these chains, each [(Tp*)Fe(CN)3]− entity binds to the NiII ion of the [Ni(L)Ln(NO3)2(H2O)]+ motif through two of its three cyanide groups in a cis mode, whereas each [Ni(L)Ln(NO3)2(H2O)]+ unit is linked to two [(Tp*)Fe(CN)3]− ions through the NiII ion in a trans mode. In the [Ni(L)Ln(NO3)2(H2O)]+ unit, the NiII and LnIII ions are bridged to one other through two phenolic oxygen atoms of the ligand (L). Compounds 1–4 are rare examples of 1D cyanide‐ and phenolate‐bridged 3d–3d′–4f helical chain compounds. As expected, strong ferromagnetic interactions are observed between neighboring FeIII and NiII ions through a cyanide bridge and between neighboring NiII and LnIII (except for NdIII) ions through two phenolate bridges. Further magnetic studies show that all of these compounds exhibit single‐chain magnetic behavior. Compound 2 exhibits the highest effective energy barrier (58.2 K) for the reversal of magnetization in 3d/4d/5d–4f heterotrimetallic single‐chain magnets.